Types of genotypes in progressive familial intrahepatic cholestasis and liver transplantation: A meta-analysis of observational studies - Rania Sakka; Hela Abroug; Sabrine Ben Youssef; Mongi Mekki; Ridha M’rad (PLoS ONE, 2026)
Background Progressive familial intrahepatic cholestasis (PFIC) refers to a group of inherited cholestatic liver diseases that affect children, often leading to liver failure and requiring liver transplantation (LT). Many studies have established correlations between the effect of the causal gene variant types and the severity of the PFIC phenotype, the treatment considered, or its outcomes in patients. Nevertheless, no selection criteria for LT based on genotypes have been adopted for patients affected by this group of diseases. Therefore, we conducted a meta-analysis to investigate the association between the main PFIC subtype genotypes and the treatment with LT. Methods Online databases were searched for articles on PFIC1–4 and LT. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. The genotypes of patients were extracted from the included studies and categorized into a group of cases, harboring null genotypes, and a group of controls, harboring non-null genotypes. The relationship between the genotype type and LT outcome was expressed as an OR by assessing the LT event among the case group and the control group. Results Eighteen studies involving 420 PFIC patients were included. A random-effects model was used to assess the OR. Overall, we observed a close relationship between the PFIC null genotype and the LT event; OR=2.79 (95% CI:1.63 to 4.77; p < 0.001). Subgroup analysis according to the PFIC subtype showed the same effect. Conclusions Our results provide evidence of a potential association between null genotypes in PFIC diseases and the indication of LT as a treatment. Further trials are needed to confirm our results and guide decisions regarding personalized and early preventive LT. Research protocol registration https://doi.org/10.17605/OSF.IO/MNQWB